A Metaphorical Expressions on Justin Timberlake’s Songs - Miftakhul Nur Rochma; Virny Melisa Irwandi (International Consortium of Education and Culture Research Studies, 2020)
The purpose of this article is to analyze the types of metaphors and analyze the meaning in the lyrics of the song